Microelectronic circuit design - Richard C. Jaeger (McGraw-Hill Higher Education, 2008)
Richard Jaeger and Travis Blalock present a balanced coverage of analog and digital circuits; students will develop a comprehensive understanding of the basic techniques of modern electronic circuit design, analog and digital, discrete and integrated. A broad spectrum of topics are included in "Microelectronic Circuit Design" which gives the professor the option to easily select and customize the material to satisfy a two-semester or three-quarter sequence in electronics. Jaeger/Blalock emphasizes design through the use of design examples and design notes. Excellent pedagogical elements include chapter opening vignettes, chapter objectives, 'Electronics in Action' boxes, a problem-solving methodology, and 'Design Note' boxes. The use of the well-defined problem-solving methodology presented in this text can significantly enhance an engineer's ability to understand the issues related to design. The design examples assist in building and understanding the design process